COMPARISONS OF FIBRO Q INDEX AND FIB-4 IN VARIOUS STAGES OF CHRONIC B HEPATITIS - Evy Adrianti; Liong Boy Kurniawan; Ibrahim Abdul Samad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Fibro Q and FIB-4 index are non-invasive biomarkers to evaluate liver fibrosis in chronic hepatitis. This study aimed to evaluate and compare the diagnostic accuracies of Fibro Q and FIB-4 index compared with fibroscan in chronic B hepatitis. This research was a cross-sectional study including 145 patients with chronic B hepatitis who had a fibroscan examination at the Dr.Wahidin Sudirohusodo Hospital during July 2014-June 2016. The clinical data included sex, age, Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), platelet, Prothrombin Time (PT)/International Normalized Ratio (INR). Fibro Q and FIB-4 index were compared with fibroscan to predict various fibrotic degrees of chronic B hepatitis patients. There were significant differences compared to fibroscan, the highest Fibro Q average was found in the medium degree of fibrosis and the lowest in the normal fibroscan (p<0.01) while the highest FIB-4 average was found in the high degree of fibrosis and the lowest in the normal fibroscan (p<0.001). Fibro Q sensitivity and specificity test against fibroscan have AUC value of 0.579 by using a 9.33 cut-off with a sensitivity of 80.5% and specificity of 28.1%, while FIB-4 has AUC value of 0.723  by using cut-off 14.31 with sensitivity 80.5% and specificity 46.9%. These results show that both Fibro Q and FIB-4 index can be used to assess liver cirrhosis as well as fibroscan. FIB-4 Index has a better diagnostic value compared to Fibro Q, so this marker can be used as a simple screening instrument.